Diverse application platform for hard X‐ray diffraction in SACLA (DAPHNIS): application to serial protein crystallography using an X‐ray free‐electron laser. (16th April 2015) - Tono, Kensuke; Nango, Eriko; Sugahara, Michihiro; Song, Changyong; Park, Jaehyun; Tanaka, Tomoyuki; Tanaka, Rie; Joti, Yasumasa; Kameshima, Takashi; Ono, Shun; Hatsui, Takaki; Mizohata, Eiichi; et al.
<x xml:space="preserve">Abstract</x> An experimental system for serial femtosecond crystallography using an X‐ray free‐electron laser (XFEL) has been developed. It basically consists of a sample chamber, fluid injectors and a two‐dimensional detector. The chamber and the injectors are operated under helium atmosphere at 1 atm. The ambient pressure operation facilitates applications to fluid samples. Three kinds of injectors are employed to feed randomly oriented crystals in aqueous solution or highly viscous fluid. Experiments on lysozyme crystals were performed by using the 10 keV XFEL of the SPring‐8 Angstrom Compact free‐electron LAser (SACLA). The structure of model protein lysozyme from 1 µm crystals at a resolution of 2.4 Å was obtained.